PENENTUAN MEDIA PROMOSI DENGAN METODE ANALYTIC NETWORK PROCESS (ANP) (Studi Kasus : STMIK PELITA NUSANTARA MEDAN) - Bosker Sinaga (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Analytic Network Process (ANP) is a method used to find the optimal alternative of a number of alternatives to certain criteria. Selection or the process is done by evaluating the media campaign by distributing questionnaires to students to find out what media will be evaluated further by choosing 4 media campaigns, determines the criteria and sub-criteria by distributing questionnaires to the Chairman of STMIK Pelita Nusantara Medan, Wakil Ketua III of Student and Promotion Affairs and Chairman of Promotion Affairs, further it is performed data processing with the assistance from Super Decisions 2.4.0 software. Which the highest rating obtained results of the analysis and discussion shows that the Internet (0.329).This study concludes that for the promotion media selection of STMIK Pelita Nusantara Medan, Analystic Network Process (ANP) method can be applied with the use of Super Decision 2.4.0. Software, And from the results of questionnaire data processing distributed in the management of STMIK Pelita Nusantara Medan namely Chairman STMIK Pelita Nusantara Medan, Wakil Ketua III Student Affairs and Promotion, and Chairman of the Promotion STMIK Pelita Nusantara Medan, and application of Analystic Network Process (ANP) methods with the use of Super Decisions 2.4.0 Software produces the highest rank of media namely the Internet (0.329), followed by Visits to Schools (0.274), Radio (0.213), and Banners / Billboards (0.185).Keywords: Selection of Promotion Media, criteria, evaluation, Super Decisions 2.4.0.